SOME LEADERSHIP EXPERIENCES OF THE PARTY HUNG YEN PROVINCE IN THE WORK OF CONSTRUCTION OF PARTY FACILITIES. - Nguyen Thi Thu Huong (Journal of Applied Science and Technology, 2019)
Party grassroots organization (TCCSĐ) - Grassroots Party, grassroots party is the foundation of the Party, is the political core leading all aspects of the grassroots. The organization has a particularly important position in leading and organizing the successful implementation of the Party’s line in the grassroots and contributing to perfecting the Party’s line. The lessons learned in the construction of grassroots organizations in Hung Yen province are to contribute to clarify the leadership activities of the Provincial Party Committee and as a basis for the construction of the grassroots organizations in Hung Yen in the next periods.